Ensuring effective counteraction to biological threats through the prism of biorisk design - Kravchuk, Mariana; Metelskyi, Ihor (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
The scientific article is devoted to the study of the classification of biorisks on the basis of their characteristic features. This objective need is due to the important issue of ensuring a constructive approach to improving the effectiveness of a set of measures to combat bioterrorism, optimizing methods and techniques, means and methods of its use in practice of prevention and cessation of bioterrorist acts. It should also be noted that when researching the issue of biological risks, neither in the regulatory framework of Ukraine nor in international law, we do not find a comprehensive list of all types of hazards of biological origin formed and approved by the state. That is why the scientific study of this issue is relevant both theoretically and practically, as this knowledge will provide an opportunity to make the right choice of specific and effective administrative and legal measures to ensure biosafety. The study emphasizes that the relevant sources of danger of biological origin hide in themselves and under certain conditions by themselves or in various aggregates have a negative impact on society, pose a threat to human development and can lead to loss of human resources. These dangerous factors directly affect both the socio-political and socio-economic situation of the country, which, in turn, ensures the compliance of the human environment and its living needs. The consequences of such a danger can be a decline in living standards, loss of property, capital, work, income, investment, and so on. In addition, we should not forget about such basic parameters of the social environment as the need to receive services in the field of education, health, culture, social protection. It is concluded that today the latest pathogens, products of modern biotechnology, are constantly appearing, and, accordingly, the above classification of biorisks should not be taken as a dogma. Moreover, other approaches can be used in the study of this issue. However, the value of the authors of the list of biorisks is to minimize or eliminate them.